2021
DOI: 10.4103/lungindia.lungindia_589_20
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and pulmonary exacerbations in children and adolescents with cystic fibrosis

Abstract: Background: The function of Vitamin D in preventing inflammation and infection has been studied previously for different pathologies in different populations globally. Relationships between serum Vitamin D levels and its effect on pulmonary exacerbations in the cystic fibrosis (CF) population are not well studied in our part of the world. Therefore, we aimed to ascertain the Vitamin D status in pediatric and adolescent CF patients and its association with pulmonary exacerbations. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…In contrast with our study, Sexauer et al studied 597 patients with a mean age of 22.2 ± 11.9 years, observing a significant relationship between serum levels of vitamin D and pulmonary function in CF patients (9). In addition, a study in Pakistan showed that 69 CF patients were deficient in vitamin D. Vitamin D deficiency was also associated with an increase in the number of annual pulmonary exacerbations and Pseudomonas infections (21). Moreover, Vanstone et al indicated that depleted vitamin D status was a significant cause of developing pulmonary exacerbations (22).…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast with our study, Sexauer et al studied 597 patients with a mean age of 22.2 ± 11.9 years, observing a significant relationship between serum levels of vitamin D and pulmonary function in CF patients (9). In addition, a study in Pakistan showed that 69 CF patients were deficient in vitamin D. Vitamin D deficiency was also associated with an increase in the number of annual pulmonary exacerbations and Pseudomonas infections (21). Moreover, Vanstone et al indicated that depleted vitamin D status was a significant cause of developing pulmonary exacerbations (22).…”
Section: Discussioncontrasting
confidence: 95%
“…All articles were published between 1981 and 2018. Among the studies integrated in this systematic review, 8 studies were case–control [ 21 28 ] and 12 studies had a cross-sectional design [ 29 40 ]. The total sample size was 1,157 in the case control studies and 1622 patients in the cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…J Chin Endocrunol 197 l;33:992–5.) YES YES 6 Jakovska et al [ 26 ] 2018 Macedonia stable CF children 8.25 ± 1.9 7.5 ± 1.9 35 23/8 ± 10.9 21 25/6 ± 11.5 Electrohemiluminiscent method NO NR 7 Stead et al [ 29 ] 1988 London CF Both The mean daily intake of vitamin D was 19 1 jg (764 IU), range 0 6–54 3 pg (24–2172 IU). Only seven of the 31 patients were not taking supplements of vitamin D All or some received vitamin D supplements 25/5 24.…”
Section: Resultsmentioning
confidence: 99%
“…McCauley LA et al found that adolescents aged 15-18 years with vitamin D deficiency had a higher rate of exacerbations than those with insufficient or sufficient levels of vitamin D, 13 per 10 patient-years (95% CI, 6-31; p < 0.05) vs. 4.3 per 10 patient-years (95% CI, 2-8; p < 0.05), respectively [149]. A report by Aziz D et al of 69 children with CF aged 3 to 18 years found that children with vitamin D deficiency had significantly more pulmonary exacerbations per year than patients with insufficient or sufficient levels (n = 28, 3.71 ± 0.96; n = 22, 3.18 ± 1.09; and n = 19, 2.26 ± 0.93; respectively; p < 0.001 [145]. In another study, 148 children from 10 months to 12 years of age were evaluated for inflammation and bacterial colonization.…”
Section: The Presence Of Inadequate and Deficient Levels Of Vitamin D...mentioning
confidence: 93%
“…A child with cystic fibrosis (CF) is likely to have insufficient or deficient levels of fat-soluble vitamins because of the malabsorption of fat-soluble vitamins caused by exocrine pancreatic insufficiency, poor nutritional intake, changes in metabolism, and other factors [99,145,146]. These vitamins are routinely supplemented to CF patients to avoid deficiencies.…”
Section: Cystic Fibrosismentioning
confidence: 99%